Learning at home: Parents’ lived experiences on distance learning during COVID-19 pandemic in the Philippines - Casper Boongaling Agaton; Lavinia Javier Cueto (International Journal of Evaluation and Research in Education (IJERE), 2021)
COVID-19 pandemic has closed-down educational institutions and dramatically shifts the instruction to distance learning. However, students rooted from the marginalized families and from rural areas have limited access to technology necessary for online learning. Modular learning addresses this learning inequality by providing more inclusive access to education. This study explored the lived experiences of the parents who act as learning supervisor, tutor, and home-schooling teacher for modular learning during the health crisis. This research surveyed parents from the Philippines and applied Inductive Content Analysis. The results showed an agreement on the effectiveness of the implemented educational policies to contain the pandemic including the nationwide closures of schools, delaying the reopening of classes, and implementation of various instructional modalities. On the other hand, parents have encountered various challenges from the new mode of learning in virtual setting; delivery of instruction; unsatisfactory learning outcomes; financial difficulties while working for the family during lockdown; struggle with the use and availability of technology; and personal problems on health, stress, and learning style. This study serves as a basis for providing a comprehensive and inclusive education policies while considering the perspective of the learners’ parents during the pandemic and beyond.